Inhibition of Autism Spectrum Disorder Associated Bacteria and C. difficile by Polyols - ML, Cannon; M, Merchant; W, Kabat; B, Unruh; A, Ramones (Edelweiss Applied Science and Technology, 2020)
Objectives: To determine the effectiveness of erythritol and xylitol in the inhibition of gut bacteria possibly associated with Autism Spectrum Disorder (ASD) and Clostridium difficile Infection (CDI). Methods: Seven bacterial strains associated with ASD, or with CDI and a control probiotic were tested for polyol inhibitory activity: Clostridium histolyticum, Bacteroides vulgatus, Bifidobacterium longham, and two strains each of Clostridium bolteae and difficile. Each strain was grown in brain heart infusion/sucrose media with polyol concentrations varying from 0% to 15% for erythritol and 0% -30 % for xylitol. Growth of Clostridium histolyticum and Bifidobacterium longham was measured after 24 hours while all other strains were evaluated at 48 hours to permit additional growth. Optical density was measured using a spectrophotometer and the plates were read at 620 nm. Results: All strains had results indicating polyol inhibition of growth. Clostridium histolyticum (Chis), Bifidobacterium longham (Blof), and both Clostridium bolteae (Cbol) strains showed reduced growth with increasing polyol concentration with an inflection point of about 4% for both xylitol and erythritol (complete or near complete inhibition relative to control wells). Bacteroides vulgatus (Bvul) grew very lightly in the BHI/sucrose. This strain has visible growth but very low OD values. Inhibition of growth with increasing polyol concentrations was observed but assessing the polyol inhibition break point was difficult with this strain. Conclusions: Xylitol and erythritol at sufficient concentrations were able to inhibit the growth of bacterial strains that have been associated with the development of Autism Spectrum Disorder in recently published studies.